High electrical conductivity of nanocomposites based on Ce0.82Sm0.16Sr0.02O1.90 and (Li/Na)2 CO3 for low temperature solid oxide fuel cells - Jaiswal N.; Kumar D.; Upadhyay S.; Parkash O. (My University, 2025)
Ce0.82Sm0.16Sr0.02O1.90 (SSDC) based nanocomposites with different weight ratio of the eutectic mixture of Na2CO3-Li2CO3 have been prepared by mixing nanocrystalline powders of co-doped ceria with the carbonates. Single phase formation has been confirmed using X-ray diffraction (XRD). Samples sintered at 700 °C are characterized by scanning electron microscope (SEM), energy dispersive spectroscopy (EDS), thermal expansion and impedance analysis. SEM micrographs show a homogeneous distribution of both the phases. A sharp jump in the conductivity has been observed in all the composites at a particular temperature. This is attributed to a superionic transition at the interfaces formed between the ceria and the carbonate phases. Conductivity of the composites increases with increasing the carbonate content due to increase in the interfacial area between the two phases. Composition containing 35 wt% of the carbonates shows the maximum conductivity, 7.48×10-2 S-cm-1 at 500 °C with activation energy of conduction 0.48 eV. This value is one order of magnitude more than that of SSDC. © 2016 Elsevier Ltd and Techna Group S.r.l. All rights reserved